2018
DOI: 10.3847/1538-3881/aaa085
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Approach to Model the Spectra and Radiation Dose Rate of Solar Particle Events on the Surface of Mars

Abstract: For future human missions to Mars, it is important to study the surface radiation environment during extreme and elevated conditions. In the long term, it is mainly Galactic Cosmic Rays (GCRs) modulated by solar activity that contributes to the radiation on the surface of Mars, but intense solar energetic particle (SEP) events may induce acute health effects. Such events may enhance the radiation level significantly and should be detected as immediately as possible to prevent severe damage to humans and equipm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 55 publications
7
44
0
Order By: Relevance
“…The MARSIS instrument in particular has been making ionospheric sounding measurements of the Martian topside ionosphere, which can be used to infer the vertical electron density profiles of the topside ionosphere. During the SEP event period, MARSIS detected ionospheric echoes with unusually high peak electron densities (∼1–2 ×10 4 cm −3 ) at ∼120‐km altitudes in the deep nightside ionosphere, suggesting enhanced impact ionization by precipitating energetic particles (e.g., Guo, Zeitlin, et al, ; Norman et al, ; Withers, ). Associated with high SEP fluxes, MARSIS also observed the disappearance of ground reflection due to radio wave attenuation (i.e., radio blackout periods) by enhanced ionization below the peak density altitude of ∼100–150 km (Fowler et al, ; Girazian et al, ).…”
Section: Seps At Marsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MARSIS instrument in particular has been making ionospheric sounding measurements of the Martian topside ionosphere, which can be used to infer the vertical electron density profiles of the topside ionosphere. During the SEP event period, MARSIS detected ionospheric echoes with unusually high peak electron densities (∼1–2 ×10 4 cm −3 ) at ∼120‐km altitudes in the deep nightside ionosphere, suggesting enhanced impact ionization by precipitating energetic particles (e.g., Guo, Zeitlin, et al, ; Norman et al, ; Withers, ). Associated with high SEP fluxes, MARSIS also observed the disappearance of ground reflection due to radio wave attenuation (i.e., radio blackout periods) by enhanced ionization below the peak density altitude of ∼100–150 km (Fowler et al, ; Girazian et al, ).…”
Section: Seps At Marsmentioning
confidence: 99%
“…With no global magnetic field at Mars to deflect the charged particles nor a thick atmosphere to shield against them, SEPs with energies of 150 MeV/nuc and higher can penetrate down to the surface (Guo, Zeitlin, et al, ; Hassler et al, ). The detection of such an event at Mars is analogous to the ground‐level enhancement (GLE) event that occurs at Earth when ground‐based instruments detect secondary neutrons caused by high energy protons impacting the top of Earth's atmosphere.…”
Section: Seps At Marsmentioning
confidence: 99%
“…It has been extensively calibrated with a variety of experiments worldwide (Agostinelli et al 2003). The tool is also used in planetary sciences to model charged particle interactions with the atmosphere (Atri 2017;Guo et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Space weather events, such as stellar flares, CMEs, and Stellar Proton Events (SPEs), abruptly bombard the planet with non-thermal radiation consisting of X-rays, EUV (XUV), and Stellar Energetic Particles (SEPs). Space weather has a significant impact on planets, with atmospheric effects such as erosion (Jakosky et al 2015), photochemical changes (Atri et al 2010;Segura et al 2010;Tabataba-Vakili et al 2016;Scheucher et al 2018), and enhanced radiation dose on the surface (Atri & Melott 2014;Atri 2017;Guo et al 2018). Earlier studies have shown that stellar flares have the capacity to significantly alter habitable conditions on planets (Airapetian et al 2017;Atri 2017;Lingam & Loeb 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation